A LINK BETWEEN ADMINISTRATION AND CREATIVITY? - Butt, Richard (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1973)
Since it is generally assumed that creativity is desirable, the question arises of how can schools be improved to foster its development. To investigate one aspect of this problem, a study was undertaken by the writer. The purpose of this research was to examine longitudinally, the relationship between the creativity of elementary school children and the school organizational climate to which they had been exposed. The instruments utilised to gather data were the Organizational Climate Descriptive Questionnaire and the Torrance Tests of Creativity (Verbal Form A).4 The O.C.D.Q. describes the behavioral interaction of a school's faculty. This interaction can be classified along a continuum of climates: Open, Autonomous, Controlled, Familiar, Paternal, Closed. Also, there are eight subtests of climate, four of which pertain to the behavior of teachers as a group: Disengagement, Hindrance, Esprit, Intimacy; and four which pertain primarily to the principal's behavior: Aloofness, Production Emphasis, Thrust, and Consideration. Torrance's Tests of Creativity sampled the creative traits of Fluency, Flexibility, and Originality on seven parallel tasks.